Monetary correction and housing finance in Colombia, Brazil, and Chile - Sandilands, Roger J. (Farnborough, Eng. : Gower, 1980)
The book examines the rationale of indexing or monetary correction schemes as advanced in the economics literature on housing finance. Three Latin American countries which have been prone to high and unstable rates of inflation namely Brazil, Colombia and Chile were studied.
Includes index.
Bibliography: p. 174-178.
usc 23/01/2019
Loans
Keywords: Housing--Finance; Indexation (Economics); Chile; Colombia; Brazil